Strengthening Discipline Character Value of Students During The Covid-19 Pandemic - Ali Sunarso; Winda Khoirunnisa (Mimbar Ilmu, 2023)
There are problems encountered in this study, namely in cultivating student discipline character values, including limited interaction, differences in students' ability to control emotions, an environment that is not conducive, limited learning facilities, and parental assistance that still needs to be improved. This study aimed to analyze efforts to instill the disciplinary character values of fourth-grade elementary school students during the COVID-19 pandemic. This study uses a descriptive qualitative research method. The subjects of this study were 23 people, including 3 class teachers, 3 student guardians, and 17 fourth-grade elementary school students. Data collection techniques are used in the form of observation, interviews, and documentation. The data analysis techniques performed were data reduction, presentation, and inference. The results of this study are that students can manage their study time at home well, study diligently and regularly, pay good attention while studying in class, and be orderly during the learning process in class, which is manifested by the efforts made by teachers and parents by habituating, mentoring, and reinforcement.